2021
DOI: 10.3390/su13031264
|View full text |Cite
|
Sign up to set email alerts
|

Green Energy, Economic Growth and Environmental Quality Nexus in Saudi Arabia

Abstract: This article extends the previous studies on environmental economics literature by examining a possible relationship between economic growth, green energy, and environmental quality. Specifically, this article investigated the three-way linkage between economic growth, renewable energy, and environmental quality in the case of Saudi Arabia using the simultaneous equation modeling approach over the period of 1990–2016. The following are the main findings obtained: (i) a unidirectional causal impact of economic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 80 publications
5
26
0
Order By: Relevance
“…The authors of this study conclude that economic growth might affect the carbon emission of countries, but its magnitude may be different for different levels of economic development for each country. Similar studies are presented by Chontanawat [62] for Southeast Asian countries, by Leitao and Lorente [63] for European countries, by Rahman et al [64] for BRICS members, and by Kahia et al [65] for Saudi Arabia.…”
Section: Kasman Andsupporting
confidence: 77%
“…The authors of this study conclude that economic growth might affect the carbon emission of countries, but its magnitude may be different for different levels of economic development for each country. Similar studies are presented by Chontanawat [62] for Southeast Asian countries, by Leitao and Lorente [63] for European countries, by Rahman et al [64] for BRICS members, and by Kahia et al [65] for Saudi Arabia.…”
Section: Kasman Andsupporting
confidence: 77%
“…Moreover, the globalization index (KOF) presents a negative effect on CO 2 emissions, showing that globalization stimulates environmental improvements. In line with the previous studies, Kahia et al (2021) evaluate the determinants of air quality and economic growth in Saudi Arabia for the period 1990-2016. Considering the equation for the carbon dioxide emissions determinants, the authors showed that income per capita and squared income per capita are according to the hypotheses of EKC.…”
Section: Economic Growth International Trade and Climate Changementioning
confidence: 68%
“…Formally, model 2 has the following econometric specification: where t ( t = 2000,…..,2018) denotes the time period, ln is the natural logarithm, CO is CO 2 emissions, Hexp is public health expenditure, R&D is research and development, and X is the vector of control variables (economic growth, energy consumption, and trade openness). We expect that these control variables increase CO2 emissions (Ben Youssef et al 2016; Omri et al 2021 ; Kahia et al 2021 ; Omri and Saidi 2022 ).…”
Section: Methodsmentioning
confidence: 99%